Underwater Acoustic Environment of Coastal Sea With Heavy Shipping Traffic: NE Baltic Sea During Wintertime - Syrjälä, Joonas; Kalliola, Risto; Pajala, Jukka (Frontiers in Marine Science, 2020)
Shipping is the most pervasive source of anthropogenic underwater continuous noise and local intermittent noise. This study focused on the separation of anthropogenic intermittent noise from dynamic background noise in the Gulf of Finland using an adaptive threshold level (ATL) technique. The intermittent noise was validated with Automatic Identification System (AIS) data and the background noise with selected environmental factors. Separated components were characterized and compared with a sound exposure level (SEL) in three 1/3 octave bands. Intermittent noise can be separated with ATL in the Baltic Sea, and vessel traffic identified as the primary source. Background noise varies spatially and is partially explained by environmental factors. Intermittent noise has strong persisting influence on the acoustic environment near shipping lanes, elevating the SEL in each of the 1/3 octave bands: by 20–30 dB in the 63 Hz band, by 13–22 dB in the 125 Hz band and by 5–8 dB in the 2000 Hz band. We conclude that strong intermittent noise is characteristic to the underwater acoustic environment in the study area with heavy shipping traffic. By combining ATL with data from AIS, intermittent noise peaks in underwater hydrophone recordings can be associated with passages of individual vessels.